Effect of Workload and Nurse Competency on Patient Safety Incidents and Application of 6 Patient Safety Goals as Intervening Variables - Feggy Ekatama Anggela; Mohamad Reza Hilmy; Kemala Rita Wahidi (Jurnal Health Sains, 2023)
Patient safety is something that needs to be prioritized in health services. The goal of this study was to examine nurses' workload and competence on patient safety incidents using the six patient safety goals as intervening variables. a cross-sectional study at a private hospital in Tangerang in February 2022. The research subjects were all functional nurses in the hospital. There is an influence between workload, nurse competence, and implementation of the 6 patient safety goals on patient safety incidents (p<0.001). Low workload and high nurse competence can improve the implementation of the six patient safety goals, which will reduce patient safety incidents.